A selection of the poems of Sir Constantijn Huygens (1596-1687) - Huygens, Constantijn 1596-1687 (Amsterdamse Gouden Eeuw reeks, 2015)
Dutch Golden Age poet Constantijn Huygens (1596-1687) was a remarkable figure: in addition to writing poetry, he composed music; was secretary to two Princes of Orange, Frederick Henry and William II; and became a friend to John Donne, Rembrandt, Descartes, and many other notable people of his time. In this book, Peter Davidson and Adriaan van der Weel offer a broad selection of Huygens's poems and provide excellent translations for those written in Dutch, Latin, and a number of other languages revealing both Huygens literary talent and his remarkable linguistic range